PENGARUH METODE TUTOR SEBAYA (PEER TEACHING METHOD) TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS IV SDN 1 KAWO TAHUN AJARAN 2021/2022 - Selvia Putri Arsanti; Husniati Husniati; Heri Setiawan; Mansur Hakim (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
This research aimd to find the influence of Peer Teaching Method students poetry writing skill at IV grade students of SDN 1 KAWO in academic year 2021/2022. The method used in this research is quasi experiment with research Nonequivalent Control Group Design. Sampling used a saturated sampling technique. The sample of this research is 38 students. In the control class used conventional methods and in the experimental class used Peer Teaching Method. The instrumen used to collect data is the skill of writing poetry by using rubric and observation sheet. the data obtained were tested by using t-test formula that is test Polled Variance at 5% significant level. The results showed that the average value of Pretest experimental class is 61 and the average Pretest grade of control is 55,1. After the action done in both classes, the average of posttest of experiment class obtained is 74,4 and control class is 62,7. Result of t-count of hypotesis test in experiment control class are -0,015, while result of ttable by using interpolation formula is -2,662 Based on the result of hypothesis testing, it is obtained tcount ≥ ttable at a significant level of 5%, then HO is rejected and Ha is accepted. Therefore it can be concluded that the use of peer teaching method influenced the skill of poerty writing at IV grade student of SDN 1 Kawo in academic year 2021/2022.